Bachelor Course in Military Sciences: construction and mobilization of teaching knowledge (Práxis Educativa, 2023)
This work presents the process of construction and mobilization of knowledge and expertise inherent to teaching in a military teaching institution. This is a case study in the Bachelor Course in Military Sciences – Prevention and Management of Disasters of the Minas Gerais Military Firefighter Academy, Brazil. As a result, in general, the instructors learned how to be a teacher during the teaching practice, and the experiences lived in the work environment of an operational level were taken to the classroom, directly influencing the teaching process. The construction process of the teaching identity is linked to several factors, whether related to human individuality, awareness of the real function of being a teacher and what the act of teaching would be in itself, or factors linked to experiential, pedagogical, curricular and disciplinary knowledge.Keywords: Military Education. Firefighter Training. Teaching knowledge.